Pengaruh Likuiditas dan Solvabilitas Terhadap Rentabilitas Ekonomis pada Koperasi Sawit Usaha Manunggal Desa Seresam Kecamatan Seberida Kabupaten Indragiri Hulu - Irawati Irawati; Fitria Ningsih (J-MAS (Jurnal Manajemen dan Sains), 2020)
This research was conducted at Manunggal Palm Oil Cooperative in Seresam Village, Seberida District, Indragiri Hulu Regency. Researchers. The research was started from 2013 to 2018. The analysis applied the quantitative method with Multiple Linear Regression, Correlation Coefficient and determination and then testing the hypothesis using SPSS Version 21. The result of this research is that liquidity has no effect on economic profitability. While solvency affects economic rentability.While simultaneous liquidity and solvency affect economic profitability.